Exports and Innovation in Malaysia: the role of Heterogeneity - YuanFang Chen; Lim Thye Goh (Indonesian Journal of Economics, Social, and Humanities, 2021)
The objective of this paper was to empirically examine the impact of exports on the level of innovation in the manufacturing sector of Malaysia and to focus on the role of heterogeneity in exports by using detailed industry-level cross-sectional data on Malaysia’s manufacturing sector in 2014. Utilising the CDM model, as postulated by Crepon, Duguet & Mairesse (1998), this paper investigated whether exporting to more countries, exporting greater volumes, and exporting greater volumes to high-income countries induced industry to increase its level of innovation. Estimates from the CDM model showed, overall, a positive impact of exports on innovation, more specifically, heterogeneity in exports mattered to industries’ innovating in the manufacturing sector in Malaysia. Additionally, exporting to additional foreign destinations, exporting greater volumes of product, and exporting more products to low-income countries, especially to South Asian and Southeast Asian countries, had a significant influence on inducing industries to engage in innovation activities.